Vitamin D status is independently associated with plasma glutathione and cysteine thiol/disulphide redox status in adults. (15th April 2014) - Alvarez, Jessica A.; Chowdhury, Ritam; Jones, Dean P.; Martin, Greg S.; Brigham, Kenneth L.; Binongo, José N.; Ziegler, Thomas R.; Tangpricha, Vin
Summary Objective Redox status and inflammation are important in the pathophysiology of numerous chronic diseases. Epidemiological studies have linked vitamin D status to a number of chronic diseases. We aimed to examine the relationships between serum 25‐hydroxyvitamin D [25(OH)D] and circulating thiol/disulphide redox status and biomarkers of inflammation. Design This was a cross‐sectional study of N = 693 adults (449 females, 244 males) in an apparently healthy, working cohort in Atlanta, GA. Plasma glutathione (GSH), cysteine (Cys) and their associated disulphides were determined with high‐performance liquid chromatography, and their redox potentials (Eh GSSG and Eh CySS) were calculated using the Nernst equation. Serum inflammatory markers included interleukin‐6 (IL‐6), interleukin‐8 (IL‐8) and tumour necrosis factor‐α, assayed on a multiplex platform, and C‐reactive protein (CRP), assayed commercially. Relationships were assessed with multiple linear regression analyses. Results Serum 25(OH)D was positively associated with plasma GSH (β ± SE: 0·002 ± 0·0004) and negatively associated with plasma Eh GSSG (β ± SE: −0·06 ± 0·01) and Cys (β ± SE: −0·01 ± 0·003) (P < 0·001 for all); statistical significance remained after adjusting for age, gender, race, percentage body fat and traditional cardiovascular risk factors (P = 0·01–0·02). The inverse relationship between serum 25(OH)D and CRP was confounded by percentage body fat, and full adjustment for covariates attenuated serum 25(OH)D relationships with other inflammatory markers to nonstatistical significance. Conclusions Serum 25(OH)D concentrations were independently associated with major plasma thiol/disulphide redox systems, suggesting that vitamin D status may be involved in redox‐mediated pathophysiology.